Pengaruh Motivasi Kerja dan Kepemimpinan Terhadap Kinerja Karyawan PT. Berkah Karunia Kreasi Prabumulih - Samsi, Romsa Endrekson; Marina, Resi (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2024)
This research aims to determine the influence of work motivation and leadership on employee performance, both partially and simultaneously. The sample consisted of 26 people who were employees at the research object company in Prabumulih City. The method used is quantitative using a questionnaire. The analysis technique used is multiple linear regression analysis based on the results of data calculations and analysis used to obtain the multiple linear regression equation Y = 8.471 + 0.526X1 + 0.274X2 + e, the results of statistical testing (t test) show that the work motivation variables (X1) and has a positive and significant effect on employee performance (Y) with a t value of 4.740 with a significance value of 0.00 <0.05, because a significant value below 0.05 shows that work motivation has a significant influence on employee performance. The leadership variable (X2) has a positive and significant effect on employee performance (Y) with a t value of 2.525 with a significance value of 0.00 < 0.05, because a significance value below 0.05 indicates that leadership has a positive influence on employee performance. . Based on a simultaneous statistical test (F test), it shows that Leadership Style (X1) and Work Motivation (X2) together influence Employee Performance (Y). This can be seen from the Fcount which is greater than the Ftable (47.862 > 2.79) value. significance is smaller than 0.05 (0.000 < 0.05). The results of the summary model output analysis showed that the determination test results gave an Adjusted R square of 0.868, this means that 86.8% of employee performance is influenced by work motivation and leadership, while the remaining 13.2% of employee performance is influenced by other variables not examined in this research.